2014
DOI: 10.1021/jf500267e
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Feasibility of Trans-Free Plastic Fats through Lipozyme TL IM-Catalyzed Interesterification of Palm Stearin and Akebia trifoliata Variety Australis Seed Oil

Abstract: Akebia trifoliata var. australis seed oil (ASO) was used as an edible oil in China. However, in-depth research studies on ASO have yet to be conducted for production of plastic fats in food industry. In this work, an immobilized lipase from Thermomyces lanuginosus (TL IM) was employed to catalyze palm stearin (PS) with different ratios of ASO in a laboratory-scale operation at 60 °C. The physical properties [e.g., fatty acid profile, slip melting point (SMP), solid fat content (SFC), polymorphic form, and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Therefore, the ratio of caprylic/capric TAG to SBO of 45:55 w/w was selected for subsequent experiments. It has also been observed in other enzymatic studies that final product formation strongly depends on the substrate ratio (Lu et al, 2017;Zhao et al, 2014). As expected, a higher ratio of caprylic/capric TAG to SBO resulted in a product that contained a higher concentration of MLCT.…”
Section: Pilot-scale Mlct Productionsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the ratio of caprylic/capric TAG to SBO of 45:55 w/w was selected for subsequent experiments. It has also been observed in other enzymatic studies that final product formation strongly depends on the substrate ratio (Lu et al, 2017;Zhao et al, 2014). As expected, a higher ratio of caprylic/capric TAG to SBO resulted in a product that contained a higher concentration of MLCT.…”
Section: Pilot-scale Mlct Productionsupporting
confidence: 82%
“…The change in fatty acids at the sn-2 position may have resulted from acyl migration of TAG species (Jeyarani and Yella Redy, 2010;Noor Lida et al, 2006;Rønne et al, 2005). Lee et al (2008) and Zhao et al (2014) also reported that the interesterification increased the saturation at the sn-2 position when Lipozyme TL IM was used as the interesterification catalyst. Acyl migration is an unavoidable side reaction during interesterification.…”
Section: Physicochemical Properties Of Mlct Productsmentioning
confidence: 99%
“…Zhao et al . () reported the β′ form increased whereas the β form decreased with increasing PS amount in interesterified fat of PS and Akebia Trifoliate Variety Australis seed oil. The β′ form is a desirable polymorph for spreadable margarine with small crystals.…”
Section: Resultsmentioning
confidence: 95%
“…Table shows that 8 out of 19 recent studies also prepared low‐ trans or trans ‐free margarines and shortenings in similar ways to the manufacturing process of NovaLipid. That is, they employed the lipase‐catalyzed interesterification of solid fats (palm stearin, fully hydrogenated soybean oil, and beef tallow) with liquid oils (soybean, high‐stearidonic soybean, high‐oleic sunflower, pine nut, and akebia oils) using a commercial immobilized nonspecific lipase such as Novozym 435 as well as Lipozyme RM IM and Lipozyme TL IM (Adhikari and others ; Li and others ; Segura and others ; Pande and Akoh ; Otero and others ; Pacheco and others ; Zhao and others ; Zhu and others ). Kim and others () reported that additional incorporation of MCFA‐rich oils into the substrates for the interesterification increases the diversity in the FA profile of resulting low‐ trans or trans ‐free margarines, thereby giving more desirable textural attributes to the products.…”
Section: Low‐trans or Trans‐free Plastic Fatsmentioning
confidence: 99%
“…The reason is because bioavailability of FAs is greater in phospholipid form than in TAG form (Lemaitre‐Delaunay and others ). Table lists examples of recent studies to enzymatically prepare n ‐3 FA‐rich phosphatidylcholine (Li and others ; Zhao and others ) and MCFA‐rich phosphatidylcholine (Ochoa and others ; Kim and Yoon ). The researchers employed phospholipase‐catalyzed interesterification or acidolysis for the structural modification of phosphatidylcholine.…”
Section: Structurally Modified Phospholipidsmentioning
confidence: 99%